2003
DOI: 10.1538/expanim.52.99
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Difference between Dietary Obesity-Susceptible and Obesity-Resistant Sprague Dawley Rats in Response to Moderate High Fat Diet.

Abstract: Abstract:The primary aim of the present study was to define central and peripheral physiological differences between dietary obesity-susceptible (DOS) and obesity-resistant (DOR) outbred Sprague Dawley (SD) rats when given a moderate high fat diet containing 32.34% of energy as a fat. After a 9-week feeding period, the DOS-SD rats consumed significantly more feed (11.1%) and had higher abdominal (39.9%) and epididymal (27.5%) fat pads than the DOR-SD rats. In addition, serum leptin and insulin levels were sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 30 publications
(29 reference statements)
1
22
0
Order By: Relevance
“…Obesity has been characterized by numerous comorbidities in addition to elevated weight and body fat, as mentioned above, including systemic insulin resistance, hyperinsulinaemia, hyperleptinaemia, hyperglycaemia, dyslipidaemia and elevated systolic arterial pressure (6,9,10,13,14). The increase in body weight and fat, due to the hypercaloric pellet-diet cycle used in this work, was associated with these co-morbidities.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Obesity has been characterized by numerous comorbidities in addition to elevated weight and body fat, as mentioned above, including systemic insulin resistance, hyperinsulinaemia, hyperleptinaemia, hyperglycaemia, dyslipidaemia and elevated systolic arterial pressure (6,9,10,13,14). The increase in body weight and fat, due to the hypercaloric pellet-diet cycle used in this work, was associated with these co-morbidities.…”
Section: Discussionmentioning
confidence: 82%
“…Therefore, the aim of this study was to develop a more controlled diet consisting of a cycle of hypercaloric pellet-dietary formulations with a different palatability to induce experimental obesity in rats. Obesity is considered to be associated with numerous co-morbidities such as a systemic resistance to insulin, hyperglycaemia, dyslipidaemia, hyperleptinaemia, hyperinsulinaemia and systemic arterial hypertension (6,9,10,13,14) and these parameters were therefore investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the differences in weight gain between these strains occurred within the first 4 wk of the dietary intervention, but beyond this time period both strains had similar weight gain patterns. Previous investigations comparing alternative animal models that are either prone or resistant to the development of obesity indicate much of these differences can be attributed to variable dietary consumption (30,32,44,45,55). In opposition to these findings, the differences in weight gain found between HCR and LCR rats cannot be explained by differences in energy intake, since both strains were consuming similar absolute amounts of energy.…”
Section: Discussionmentioning
confidence: 92%
“…However, the high-fat-induced phenotype varies distinctly, even within a group of animals with the same genetic background,9 10 and it has recently been demonstrated that disctinct gut microbiota profiles are associated with different metabolic phenotypes 11. Gut microbiota of humans and mice are more than 95% made up of three phyla: Firmicutes, Bacteroidetes and Actinobacteria.…”
Section: Introductionmentioning
confidence: 99%